2020
DOI: 10.1007/s10120-020-01121-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diagnostic value of fluorescent lymphography-guided lymphadenectomy for gastric cancer

Abstract: Background Indocyanine green fluorescent lymphography helps visualize the lymphatic drainage pattern in gastric cancer; however, it is unknown whether fluorescent lymphography visualizes all metastatic lymph nodes. This study aimed to evaluate the sensitivity of fluorescent lymphography to detect metastatic lymph node stations and lymph nodes and the risk of false-negative findings. Methods Patients with clinical T1-4a gastric cancer were included. Indocyanine green was peritumorally injected the day prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Tajima et al [ 28 ] found that intraoperative subserosal injection was less accurate than preoperative submucosal injection of ICG for detecting sentinel LNs. Moreover, some retrospective studies [ 29 , 30 ] support the use of submucosal injection of ICG for fluorescence-guided lymphadenectomy the day before surgery. These inconsistent results may be explained by the selection bias inherent in retrospective investigations and varying injection sites, time, and concentrations of ICG used across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tajima et al [ 28 ] found that intraoperative subserosal injection was less accurate than preoperative submucosal injection of ICG for detecting sentinel LNs. Moreover, some retrospective studies [ 29 , 30 ] support the use of submucosal injection of ICG for fluorescence-guided lymphadenectomy the day before surgery. These inconsistent results may be explained by the selection bias inherent in retrospective investigations and varying injection sites, time, and concentrations of ICG used across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing trials investigating the extent of lymphadenectomy after neoadjuvant therapy will allow to standardize the LN dissection from the multimodal therapy perspective (NCT02139605, NCT03961373). Fluorescence-guided lymphadenectomy is a new, feasible technique which allows to detect LN metastases within fluorescent LN stations [101,102] (Figure 1). Indocyanine green can improve the LN harvest and reduce LN noncompliance without increased complications in patients undergoing D2 lymphadenectomy [103].…”
Section: Nodal Status From the Surgical Perspectivementioning
confidence: 99%
“…76 The sensitivity of fluorescent lymphography to detect metastatic lymph nodes was 95.3%, and the negative predictive value of nonfluorescent lymph nodes to not contain metastasis lymph nodes was 99%. 76 Fluorescent image-guided gastrectomy can be useful for radical lymphadenectomy and individualized lymphadenectomy for gastric cancer. ing the aberrant left hepatic artery, deciding whether to preserve or ligate an aberrant left hepatic artery.…”
Section: Fluorescence Image-guided Gastrectomymentioning
confidence: 94%
“…Despite the results of studies, whether fluorescent lymphography detects all potentially metastatic lymph nodes remains unclear. Recently, a study to evaluate the diagnostic value of fluorescent lymphography was conducted in Korea 76 . The sensitivity of fluorescent lymphography to detect metastatic lymph nodes was 95.3%, and the negative predictive value of nonfluorescent lymph nodes to not contain metastasis lymph nodes was 99% 76 .…”
Section: Fluorescence Image‐guided Gastrectomymentioning
confidence: 99%
See 1 more Smart Citation